Information seekers' visual focus during time constraint document triage - Loizides, Fernando (My University, 2012)
Time-constraints are a commonly accepted limitation to a user's information seeking process. Physical time constraints can cause users to have a low tolerance of time consuming information seeking tasks. This paper examines the effects of time constraints on the document triage process in an eye-tracked lab-based study. The visual attention of three time constraints are reported on. Similarities and differences to previous triage data are also reported on, contributing to an ongoing research investigation of the general document triage process
Keywords: Information theory; Computer science; Digital libraries